Where faith meets modernity: cemevi and local Alevi politics - Karaömerlioğlu, M. Asım; KOUROU, NUR SİNEM (My University, 2020)
This article intends to shed light on the local politics of the Alevis by focusing on three different cemevis in Istanbul’s Gazi neighborhood. Based on a field study in the neighborhood between 2014 and 2015 and eventually revisiting it in 2019, we analyze the local political dynamics with regard to different cemevis. By so doing, we aim to acknowledge and underline two phenomena: the dialectical tension between faith and modernity as well as the fragmented nature of the Alevi identity. The latter task is crucial since most recent studies concerning Alevis have focused on their so-called ‘awakening’ or the ‘discovery’ of their identity. We look at the other side of the coin as well, namely the fragmentation of Alevi identity that has also been under way in recent decades. By this means, we hope to contribute to the literature on contemporary Alevi identity and politics.
Keywords: Alevis; Cemevi; Minorities in Turkey; Public sphere; Identity politics in turkey; Religion and politics in Turkey